DETERMINANTS OF BANK PROFITABILITY: EVIDENCE FROM THE GREEK BANKING SECTOR - Alexiou, Constantinos; Sofoklis, Voyazas (Economic Annals, 2009)
This paper investigates the effects of bank-specific and macroeconomic determinants of bank profitability, using an empirical framework that incorporates the traditional Structure-ConductPerformance (SCP) hypothesis. A panel data approach has been adopted and effectively applied to six Greek banks. The evidence generated suggests that for any consistent or systematic size the profitability relationship is relatively weak. Most of the bank-specific determinants were found to significantly affect bank profitability. A more ambiguous picture emerged when the macroeconomic factors were considered.